Effect of Non-canonical Spatial Symmetry on Subitizing - Hsin, Chih-Yen; Lo, Yu-Hui; Tseng, Philip (Frontiers in Psychology, 2021)
Subitizing refers to people’s ability to accurately and effortlessly enumerate a small number of items, with a capacity around 4 elements. Previous research has shown that “canonical” organizations such as familiar layouts on a dice can readily improve people’s subitizing performance. However, almost all canonical shapes found in the world are also highly symmetrical, therefore it is unclear whether previously-reported facilitative effect of canonical organization is really due to canonicality, or simply driven by spatial symmetry. Here we investigated the possible effect of symmetry on subitizing by using symmetrical, yet non-canonical, shape structures. These symmetrical layouts were compared with highly-controlled random patterns (Experiment 1), as well as fully-random and canonical patterns (Experiment 2). Our results showed that symmetry facilitates subitizing performance, but only at set size of 6, suggesting that the effect is insufficient to improve people’s performance in the lower or upper range. This was also true, though weaker, in RT, error distance measures, and Weber Fractions. On the other hand, canonical layouts produced faster and more accurate subitizing performances across multiple set sizes. We conclude that although previous findings have mixed symmetry in their canonical shapes, their findings on shape canonicality cannot be explained by symmetry alone. We also propose that our symmetrical and canonical results are best explained by the “groupitizing” and pattern recognition accounts, respectively.